Lymphaticovenular Anastomosis: Superficial Venous Anatomical Approach - Winaikosol, Kengkart; Surakunprapha, Palakorn (Archives of Plastic Surgery, 2022)
Background Lymphaticovenular anastomosis (LVA) is an effective, functional treatment for limb lymphedema. This study reports an alternative surgical approach to lymphedema treatment without the use of indocyanine green mapping.Methods A retrospective analysis was performed on 29 consecutive lymphedema patients who underwent LVAs from January 2015 to December 2020, whereby incisions were made along the anatomy of the superficial venous systems in both upper and lower extremities around the joint areas. The evaluation included qualitative assessments and quantitative volumetric analyses.Result The mean number of anastomoses was 3.07, and the operative time was 159.55 minutes. Symptom improvement was recorded in 86.21% of the patients, with a mean volume reduction of 32.39%. The lymphangitis episodes decreased from 55.17% before surgery to 13.79% after surgery, and the median number of lymphangitis episodes per year decreased from 1 before surgery to 0 after surgery.Conclusions The superficial venous anatomical approach is an easy way to start a lymphedema practice using LVA without other advanced surgical equipment. With this reliable technique, microsurgeons can perform LVA procedures and achieve good results.
Keywords: microsurgery; vein; lymphedema; lymphaticovenular anastomosis; anastomosis